Studi Literasi Informasi Mahasiswa Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura - Yokhebed, Yokhebed (Universitas Sebelas Maret, 2018)
Information literacy is one of literacy component in digital age. The puspose of this research was to know the ability of students information literacy in biology education students. This research was descriptive with 172 education biology students as the subject. Data were collected using questionnaires. Based on the result of data analysis students showed the tendency to formalate information necessity was 75,73%, finding and accessing information 66,13%, choosing and sorting information 77,68%, evaluating information as needed 69,87%, and following ethics related to access and using information source 83,86%. Thus it is necessary to improve the knowledge and skills of students in finding and accessing information to support the learning process and need to practice the ability to evaluate the information as needed